Particle morphology and morphogenesis of nascent polyethylene produced with a spherical MgCl2‐supported Ziegler–Natta catalyst in slurry process. Issue 1 (23rd August 2017) - Zhang, Zhen; Qi, Meizhou; Yang, Pengjia; Fu, Zhisheng; Xu, Junting; Fan, Zhiqiang
ABSTRACT: Ethylene polymerizations were conducted in slurry process with a spherical MgCl2 ‐supported Ziegler–Natta catalyst activated by triethylaluminum, and the morphology of nascent polymer particles was observed by scanning electron microscope. Three kinds of typical microscale morphologies: nodular and rope‐like structures on the external particle surface, and nodular structures in the bulk of the particle were observed. These structures are composed of polyethylene lamellae and amorphous phase filling the space between the lamellae. There is close relation between the polymerization activity and microporosity of the particles. When the activity was higher than 1500 g PE/g Cat, large number of tiny pores appeared in the particles, and rope‐like structures appeared on their surface. Formation of the morphologies can be reasonably explained by models based on multiscale solid structure of the catalyst particle and dynamic interactions among the growing polymer phases. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2018, 135, 45679. Abstract :